KELAYAKAN BIOCARD PADA SUBMATERI TUMBUHAN PAKU KELAS X SMA - PEBUANTI PEBUANTI PEBUANTI (FKIP Universitas Tanjungpura, 2022)
This study aims to determine the feasibility of learning media Biocard and species diversity of ferns (Pteridophyta) in the natural tourism area of Riam Merasap Bengkayang. This research comprised two stages. The first stage is observing the diversity of ferns in the natural tourism area of Riam Merasap Bengkayang and the second stage is developing media Biocard based on the results of the observations. The form of this research is quantitative with a descriptive method. Samples were taken using a purposive sampling technique with multiple plot methods. The findings showed that there were 11 species of ferns found in a closed area (canopy) and 6 species in an open area. Of the two location conditions, the highest Importance Value Index (INP) is in the open area. The highest INP value in open areas is 59.790% on Nephrolepis hirsutula (Frost.) Pr, species, and the lowest INP is 6.809% on Lygodium circinatum (Burm.f.) Sw. The highest INP in the covered area is 45.465% on Stenochlaena palustris (Burm.) Bedd. species and the lowest INP is 1.460% on the Pitrogramma calomelanos, Drymoglossum piloselloides (Linn.) species, and the Diplazium eculentum (Retz.) Sw species. The media was validated by five validatory with a CVI value of 0.96 and thus Biocard is not suitable for use as a learning media.